1999
DOI: 10.1111/j.1749-6632.1999.tb09538.x
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of Tumor Cells In Vivo by Direct Injection of HSV‐Thymidine Kinase Retroviral Vector and Ganciclovir Therapy

Abstract: The introduction of therapeutic genes into proliferating tumor cells in vivo by direct intralesional injection of retroviral vectors can provide an effective and valuable approach for the treatment of a variety of solid tumor types. Efficient transduction of tumor cells in situ by direct injection was demonstrated using a retroviral vector containing the beta-galactosidase (beta-gal) gene. Ablation therapy in vivo was demonstrated using a retroviral vector containing the Herpes simplex virus thymidine kinase g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…18,19 These and our results suggest that when considering clinical protocols using targeted vectors currently under development, it may be necessary to combine anti-vascular therapies with tumour cell-directed treatments such as conventional radiotherapy or chemotherapy, 20,21 although the HSV-tk/GCV prodrug activation system is expected to be significantly more efficacious in the presence of an immune component. [22][23][24][25] Reduced growth in response to GCV treatment was also observed for breast MDA-MB-361, colon SW620 and CACO2 carcinomas with ecotropic HSV-tk transduction, the effect being more marked for the slower growing MDA-MB-361 and CACO2 tumours. The variability in the potency of response among different tumour lines is likely to be associated with differences in transduction efficiencies (there was much higher transduction efficiency in MDA-MB-361 compared with other tumours that correlated with better differential between treated and untreated MDA-MB-361 tumours).…”
Section: Discussionmentioning
confidence: 99%
“…18,19 These and our results suggest that when considering clinical protocols using targeted vectors currently under development, it may be necessary to combine anti-vascular therapies with tumour cell-directed treatments such as conventional radiotherapy or chemotherapy, 20,21 although the HSV-tk/GCV prodrug activation system is expected to be significantly more efficacious in the presence of an immune component. [22][23][24][25] Reduced growth in response to GCV treatment was also observed for breast MDA-MB-361, colon SW620 and CACO2 carcinomas with ecotropic HSV-tk transduction, the effect being more marked for the slower growing MDA-MB-361 and CACO2 tumours. The variability in the potency of response among different tumour lines is likely to be associated with differences in transduction efficiencies (there was much higher transduction efficiency in MDA-MB-361 compared with other tumours that correlated with better differential between treated and untreated MDA-MB-361 tumours).…”
Section: Discussionmentioning
confidence: 99%
“…19,20 Retroviruses and lentiviruses integrate into the host genome and there is a greater risk of integration in nontumor cells, but they are less immunogenic than adenovirus and allow prolonged TK gene expression. 21 Both viral and nonviral delivery vectors have been endowed with additional functional motifs to promote cell targeting, endosome disruption, and the efficacy of the bystander effect. 22 The risks of viral genome integration can be avoided through the use of virus-like particles (VLPs), which are analogous to natural virions but do not carry any infectious nucleic acids.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In a few cases, the HSV1-TK gene has been delivered using autologous stem cells but this approach is generally inefficient and rarely used . Microbial delivery systems have also been explored, as well as polymer-based vectors and liposomes. , However, the majority of reports have involved viral vectors, with adenovirus most often used in clinical trials because there is only a low risk of unplanned genomic integration in nontumor cells. , Retroviruses and lentiviruses integrate into the host genome and there is a greater risk of integration in nontumor cells, but they are less immunogenic than adenovirus and allow prolonged TK gene expression . Both viral and nonviral delivery vectors have been endowed with additional functional motifs to promote cell targeting, endosome disruption, and the efficacy of the bystander effect …”
Section: Introductionmentioning
confidence: 99%
“…When grown in nude mice, administration of GCV markedly demonstrated regression of tumors over control animals [44]. Fong et al demonstrated that ablation of CT26 tumor cells in situ was achieved by directly injecting high-titer HSV-TK retroviral vector preparations into the site of tumor cell inoculation followed by intra-peritoneal delivery of GCV [45]. Chondrosarcoma cells implanted into nude mice were injected with HSV-TK.…”
Section: Variations Of Original Hsv-tk Approachmentioning
confidence: 99%